Effects of a single phosphate-enriched test meal on inflammasome activity and postprandial inflammatory markers in healthy subjects. - Nier, Anika; Ulrich, Christof; Volk, Christin; Wolffgang, Marie-Charlotte; Brandsch, Corinna; Wensch-Dorendorf, Monika; Girndt, Matthias; Stangl, Gabriele I. (European Journal of Nutrition, 2024)
Purpose: The consumption of highly processed food is often associated with a high intake of inorganic phosphate. Hyperphosphatemia is accompanied by an inflammatory status in patients with chronic kidney disease. However, the immune response to high phosphorus intake in healthy individuals is largely unknown. Therefore, the aim of the present study was to evaluate the effect of a single phosphate-enriched meal on inflammasome activity and plasma levels of inflammatory markers. Methods: The analysis included 28 participants who received a single dose of either 700 mg phosphorus or a placebo with a test meal. At baseline, 4 and 8 h post-meal, plasma interleukin (IL)-6, IL-1β, IL-10, c-reactive protein (CRP), soluble IL-6 receptor (sIL-6R) and glycoprotein 130 (sgp130) levels were determined. At baseline and 4 h post-meal, peripheral blood mononuclear cells were isolated to assess inflammasome activity. Subsequently, the effect of phosphate with or without glucose on IL-6 and IL-1β gene expression and secretion in U937 monocytes was examined. Results: While both groups showed a marked postprandial increase in IL-6 plasma levels, neither plasma levels of IL-6, IL-1β, CRP, IL-10, sIL-6R, and sgp130 nor inflammasome activity were affected by phosphate compared to placebo. In U937 cells, there was also no effect of phosphate on IL-6 expression, but the addition of glucose increased it. Phosphate, however, reduced the IL-1β secretion of these cells. Conclusion: Postprandial inflammatory markers were not affected by dietary phosphate. However, IL-6 plasma levels were markedly increased post-meal, which appears to be a metabolic rather than a pro-inflammatory phenomenon. Trial registration number: ClinicalTrials.gov, NCT03771924, date of registration: 11th December 2018, retrospectively registered.